2019
DOI: 10.1111/ddi.12895
|View full text |Cite
|
Sign up to set email alerts
|

Environmental filtering governs the spatial distribution of alien fishes in a large, human‐impacted Mediterranean river

Abstract: Aim:To analyse the occurrence and abundance of native versus alien fish species in relation to climate, land use, hydrologic alteration and habitat fragmentation in a heavily invaded and human-impacted riverine ecosystem. To test whether co-occurrence patterns of native versus alien species are structured by environmental filtering or biotic associations.Location: Mediterranean, Iberian Peninsula, Ebro River catchment. Methods:We modelled freshwater fish distributions and their association with environmental c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
40
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 99 publications
5
40
1
Order By: Relevance
“…Although these New Zealand streams have seen an increase in functional diversity over the 25 year period, more intensified disturbances are likely to suppress or overturn this trend (Domisch et al., 2013; Kakouei et al., 2018). For example, an increasing number of colonizing warm water species could promote further species losses, by competitive exclusion (Buisson et al., 2008; Radinger et al., 2019). Moreover, the resilience of stream biodiversity in the face of continued global change could also be reduced if spatial insurance effects become less effective, as large‐scale disturbances promote greater synchrony among ecosystems (Shanafelt et al., 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Although these New Zealand streams have seen an increase in functional diversity over the 25 year period, more intensified disturbances are likely to suppress or overturn this trend (Domisch et al., 2013; Kakouei et al., 2018). For example, an increasing number of colonizing warm water species could promote further species losses, by competitive exclusion (Buisson et al., 2008; Radinger et al., 2019). Moreover, the resilience of stream biodiversity in the face of continued global change could also be reduced if spatial insurance effects become less effective, as large‐scale disturbances promote greater synchrony among ecosystems (Shanafelt et al., 2015).…”
Section: Discussionmentioning
confidence: 99%
“…) and Radinger et al. () used a similar approach (joint species distribution models) to analyze the relative influence of biotic interactions or environmental responses of the co‐occurrence patterns of plant communities along an altitudinal gradient and native versus alien fish species, respectively. Both studies found a higher influence of the environment as well on the association patterns observed between species.…”
Section: Introductionmentioning
confidence: 99%
“…For example, using fossil pollen taxa, Blois et al (2014) found that biotic interactions were rarely the only cause of associations between species pairs, but climatic or spatial differences among locations were more frequently related to significant co-occurrence patterns. D'Amen et al 2018) and Radinger et al (2019) used a similar approach (joint species distribution models) to analyze the relative influence of biotic interactions or environmental responses of the co-occurrence patterns of plant communities along an altitudinal gradient and native versus alien fish species, respectively. Both studies found a higher influence of the environment as well on the association patterns observed between species.…”
Section: Introductionmentioning
confidence: 99%
“…Under biological invasion, many native species are becoming confined to refuges where invasive species are still absent or scarce, and thus may hold remnant populations of high conservation value (e.g. Chapman et al, 1996;Grabowski et al, 2009;Habit et al, 2010;Radinger et al, 2019). This study provides a framework to predict the location and environmental drivers of such refuges, using geostatistical tools to model native species responses to exotic species while controlling for environmental effects and spatial dependencies across dendritic stream networks (Filipe et al, 2017;Peterson et al, 2013).…”
Section: Con Clus Ionsmentioning
confidence: 99%
“…Refuges may thus allow the persistence of at least some remnant populations of native species (e.g. Chapman et al, 1996;Grabowski, Bacela, Konopacka, & Jazdzewski, 2009;Habit et al, 2010;Radinger, Alcaraz-Hernández, & García-Berthou, 2019), making it a priority to understand where, why and how refuges can contribute to species conservation under biological invasion.…”
Section: Introductionmentioning
confidence: 99%